2014
DOI: 10.1007/s13594-014-0205-2
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Reggianito cheese ripening. Effect of increased initial ripening temperatures on biochemical and sensory characteristics

Abstract: The acceleration of cheese ripening is of major interest in the cheese industry because it is related to both product characteristics and production costs. In this study, different temperature-time combinations using elevated temperatures of 20°C within the first month of maturation were applied during Reggianito cheese ripening. Data obtained from proteolysis, lipolysis, analysis of volatile compounds and sensory analysis were considered to establish optimal ripening conditions. Principal component analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Sihufe et al [17] carried out a study to assess the impact of an increased storage temperature of 18 °C and suggested an optimal ripening period between 2 and 3 months. Later, another study also showed encouraging results when elevated temperatures of 20 °C were applied during the first month of the ripening period, showing an important reduction in storage time of 2 months [18] with a milder development of the final sensory characteristics [19].…”
Section: Introductionmentioning
confidence: 92%
“…Sihufe et al [17] carried out a study to assess the impact of an increased storage temperature of 18 °C and suggested an optimal ripening period between 2 and 3 months. Later, another study also showed encouraging results when elevated temperatures of 20 °C were applied during the first month of the ripening period, showing an important reduction in storage time of 2 months [18] with a milder development of the final sensory characteristics [19].…”
Section: Introductionmentioning
confidence: 92%